The ‘principle of equality governing the actions and counter-actions’ in Kant’s Practical Philosophy - Merle, Jean-Christophe (Con-Textos Kantianos. International Journal of Philosophy, 2015)
Kant’s “principle of equality governing the actions and counter-actions” (8:26) belongs not only to the Metaphysical Foundations of Natural Sciences (1786), but also to his practical philosophy. Kant’s Idea for a Universal History with a Cosmopolitan Purpose (1784) and On the Common Saying: That may be Correct in Theory, but it is of no Use in Practice (1793) may contribute to the understanding of the “principle of equality governing the actions and counter-actions” in the latter writing, and vice-versa. Referring to all three, this paper tries to show that, in the context of his concept of right, Kant understands the principle of the equality of action and reaction in two different senses, which he combines: a dynamic one and a legal one.